The Role of Exosomes Derived From Mesenchymal Stromal Cells in Dermatology - Quiñones-Vico, María I.; Sanabria-de la Torre, Raquel; Sánchez-Díaz, Manuel; Sierra-Sánchez, Álvaro; Montero-Vílchez, Trinidad; Fernández-González, Ana; Arias-Santiago, Salvador (Frontiers in Cell and Developmental Biology, 2021)
The skin is the largest organ of the human body and its main functions include providing protection from external harmful agents, regulating body temperature and homeostatic maintenance. Skin injuries can damage this important barrier and its functions so research focuses on approaches to accelerate wound healing and treat inflammatory skin diseases. Due to their regenerative and immunomodulatory properties, mesenchymal stem cells (MSCs) have been reported to play a significant role in skin repair and regeneration. However, it seems that the secretome of these cells and exosomes in particular may be responsible for their functions in skin regeneration and the immunomodulation field. The present review aims to gather the available information about the role of MSC-derived exosomes for both in vitro and in vivo models of different skin conditions and to highlight the need for further research in order to overcome any limitations for clinical translation.